Implementasi Metode Halaqah dalam Pembelajaran Fiqih Santri di Ma'had Al-Jami'ah UIN Raden Intan Lampung - Muhammad Fadhli; Listiyani Siti Romlah; Umi Hijriyah; Sa'idy Sa'idy; Erni Yusnita; Baharuddin Baharuddin (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2025)
The halaqah method is known as an effective traditional approach in teaching religious knowledge, especially in Islamic boarding schools, because it allows direct interaction between students and ustadz in an in-depth discussion atmosphere. This study uses a qualitative methodology, the study is included in the descriptive research category, by collecting data through observation, interviews, and documentation. The subjects of the study were students and teachers at Ma'had Al-Jami'ah UIN Raden Intan Lampung who participated in fiqh learning using the halaqah method. The results of the study showed that the halaqah method improved students' understanding of fiqh material, especially in daily worship practices. Some of the obstacles faced include time constraints and variations in the educational backgrounds of students. However, this method is considered effective in building the personality and skills of students in understanding fiqh in depth. These findings are expected to be a reference for the development of the halaqah method in other religious educational institutions.